Antagonist of indegenous Pseudomonas fluorescent against Ralstonia solanacearum in tomato (Lycopersicum esculentum) - Armaleni, Armaleni; Nasir, Nasril; Agustien, Anthoni (Metamorfosa: Journal of Biological Sciences, 2019)
Tomato ( L. esculentum ) is one of the most important vegetable crops produce in West Sumatra. In this province,  tomato are cultivated at highland regions of Solok, Padang Panjang, Tanah Datar  and Bukittinggi. Annually,  the increasing demand of this crop comes from other provinces in Sumatra and Java. This opportunity stimulate tomato’s agribusiness activity in West Sumatra. However, the crop succumb to the most destroyed  bacterial wilt disease caused by  Ralstonia solanacearum . The aims of this study to select antagonist  Pseudomonas fluorescent  as a biological control agent against   R.solanacearum.   The candidates of antagonist   P. fluorescetn  were collected from diseased tomato with  R. solanacearum’ s symptom in several tomato’s plantations in West Sumatra. Study of the antagonist was conducted from March to July 2016 at the Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences Andalas University. To find the antagonist work, each of the collected candidate was grown opposite  R. solanacearum  on Nutrient Agar medium. The result found that there were16 isolates of  P. fluorescent  occurred.  The best antagonist ability amongst the candidates was from Pfi  with diameter  zone was 4,95 cm. Keywords: tomato, Ralstonia solanacearum, Pseudomonas fluorescens, biological control agent, Pfi